2021
DOI: 10.1186/s12884-021-03760-2
|View full text |Cite
|
Sign up to set email alerts
|

The CErebro Placental RAtio as indicator for delivery following perception of reduced fetal movements, protocol for an international cluster randomised clinical trial; the CEPRA study

Abstract: Background Routine assessment in (near) term pregnancy is often inaccurate for the identification of fetuses who are mild to moderately compromised due to placental insufficiency and are at risk of adverse outcomes, especially when fetal size is seemingly within normal range for gestational age. Although biometric measurements and cardiotocography are frequently used, it is known that these techniques have low sensitivity and specificity. In clinical practice this diagnostic uncertainty results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…76 Currently the CEPRA trial investigates the role of Doppler measurements for timing of delivery in case of RFM at term. 69…”
Section: Reduced Fetal Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Currently the CEPRA trial investigates the role of Doppler measurements for timing of delivery in case of RFM at term. 69…”
Section: Reduced Fetal Movementsmentioning
confidence: 99%
“…The cerebroplacental ratio (CPR) (the ratio of MCA PI and UmbA PI) is a measure for brainsparing and it improves the sensitivity of Doppler monitoring because it already increases when its two components are still within the normal range 2,68 . It is not known how to use CPR in the monitoring management strategy for suspected FGR, for this reason multiple trials are underway such as DRIGITAT (NL6475, NTR 6663), CEPRA (NL 7557), RATIO37, TRUFFLE2 (IRAS Project ID: 266400) 69,70 …”
Section: Screening and Diagnosis Of Fgrmentioning
confidence: 99%
“…These technologies will not replace the inexpensive and readily-available method of Doppler ultrasound for CBF monitoring anytime soon, thus studies to maximize our knowledge and utilization of this tool are also warranted. The CEPRA study (Dutch Trial Registry NTR trial NL7557) is an example of how the fetal Doppler CBF monitoring field is moving forward, the goal of which is to determine the utility of CPR as an indicator for immediate delivery in pregnant people reporting loss of fetal movement ( 167 ). These types of multicenter studies are essential to have an impact on clinical practice of fetal monitoring technologies that have already been studied for many years.…”
Section: Future Directions In Cbf Monitoringmentioning
confidence: 99%
“…In the UK, the AFFIRM trial investigated the effects of an FM awareness package coupled with a standardised management protocol 5 . The ongoing CEPRA study in the Netherlands, UK and Australia aims to evaluate Cerebro Placental Ratio as an indicator for delivery in women with reduced FM 6 . None of the completed trials, however, found significant reductions in stillbirths.…”
mentioning
confidence: 99%